Awareness and Practice of Good Manufacturing Practices (GMP) among Street Food Vendors in Catarman, Northern Samar - , Mary Jane Madario; , Hannah Lea G. Pulga; , Karina Milagros C. Lim; , Flyndon Mark S. Dagalea (Archives of Current Research International, 2023)
Street food vendors play a crucial role in providing affordable and convenient food options, especially for those who need to purchase necessities in small quantities. However, ensuring food safety in these informal food businesses remains a major concern. This study aims to investigate the level of awareness and practices of good manufacturing practices among street food vendors in Catarman, Northern Samar. Using a combination of descriptive quantitative and qualitative approaches, the researchers conducted interviews with vendors at the University of Eastern Philippines Main Campus. A survey questionnaire was administered to gather accurate information, while simultaneous observations of the vendors' operations were conducted. Data analysis involved tallying, frequency calculation, percentage determination, and mean calculation. It was found that despite belonging to a single association, the vendors employed different food safety practices in their businesses. The findings highlight the importance of enhancing food safety knowledge among street food vendors and implementing effective measures to prevent food-borne illnesses. This study contributes to the body of knowledge on the subject and offers valuable insights for policymakers and regulatory agencies in improving food safety practices within the street food sector.